Eksistensi Kelompok- Kelompok Sosial Dalam Melestarikan Nilai-Nilai Budaya Di Desa Kamangta Kecamatan Tombulu Kabupaten Minahasa - Kandioh, Frangky; Lumolos, Johny; Kaunang, Markus (JURNAL ILMIAH SOCIETY, 2016)
This study did an analysis of factors such as how the existence of social groups in harmony grief still exist or maintained and developed in society the village Kamangta District of Tombulu Minahasa and how the role of the social pillars of grief in the village Kamangta District of Tombulu Minahasa in preserving cultural values , The results showed the existence of social groups in the village Kamangta District of Tombulu Minahasa is still maintained and will continue to be preserved in the form of social groups in harmony grief and harmonious family is a culture containing norms, trust and networks in preserving cultural values. Keywords : Existence, Social Grops, Cultural Values